Markers of low energy availability in overreached athletes: a systematic review and meta-analysis - Kuikman, M. A.; Coates, A. M.; Burr, J. F. (Sports Medicine, 2022)
Background: Overreaching is the transient reduction in performance that occurs following training overload and is driven by an imbalance between stress and recovery. Low energy availability (LEA) may drive underperformance by compounding training stress; however, this has yet to be investigated systematically. Objective: The aim of this study was to quantify changes in markers of LEA in athletes who demonstrated underperformance, and exercise performance in athletes with markers of LEA. Methods: Studies using a = 2-week training block with maintained or increased training loads that measured exercise performance and markers of LEA were identified using a systematic search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Changes from pre- to post-training were analyzed for (1) markers of LEA in underperforming athletes and (2) performance in athletes with = 2 markers of LEA. Results: From 56 identified studies, 14 separate groups of athletes demonstrated underperformance, with 50% also displaying = 2 markers of LEA post-training. Eleven groups demonstrated = 2 markers of LEA independent of underperformance and 37 had no performance reduction or = 2 markers of LEA. In underperforming athletes, fat mass (d = - 0.29, 95% confidence interval [CI] - 0.54 to - 0.04; p = 0.02), resting metabolic rate (d = - 0.63, 95% CI - 1.22 to - 0.05; p = 0.03), and leptin (d = - 0.72, 95% CI - 1.08 to - 0.35; p < 0.0001) were decreased, whereas body mass (d = - 0.04, 95% CI - 0.21 to 0.14; p = 0.70), cortisol (d = - 0.06, 95% CI - 0.35 to 0.23; p = 0.68), insulin (d = - 0.12, 95% CI - 0.43 to 0.19; p = 0.46), and testosterone (d = - 0.31, 95% CI - 0.69 to 0.08; p = 0.12) were unaltered. In athletes with = 2 LEA markers, performance was unaffected (d = 0.09, 95% CI - 0.30 to 0.49; p = 0.6), and the high heterogeneity in performance outcomes (I2 = 84.86%) could not be explained by the performance tests used or the length of the training block. Conclusion: Underperforming athletes may present with markers of LEA, but overreaching is also observed in the absence of LEA. The lack of a specific effect and high variability of outcomes with LEA on performance suggests that LEA is not obligatory for underperformance.